Genotyping Hungarian apricot cultivars for self-(in)compatibility by isoelectric focusing and PCR analysis - Pedryc, A.; Halász, J.; Hermán, R.; Hegedűs, A. (International Journal of Horticultural Science, 2005)
Self-incompatibility (SI) in flowering plants is a widespread genetic system that promotes out-crossing. In Prunus species the SI is a gametophytic trait, which is controlled by a single multiallelic locus, termed S-locus. S-alleles codify stylar glycoproteins with ribonuclease activity (S-RNases). Our objective was to assess the S-genotype of some Hungarian apricot varieties by isoelectric focusing of stylar RNases as well as by PCR analysis using cherry consensus primers. Consensus primers amplified one or two bands of various sizes. Primers amplifying the 1st intron gained fragments the size of which ranged from 250 to 500 bp; while those amplifying the 2nd intron resulted in fragments of 800-2000 by length. Our data demonstrated that the first intron of the apricot S-RNase gene is shorter than the second one, which coincides with the structure of cherry S-RNase alleles. `Hargrand' (S1S2) and `Harcoe (S1S4) possessed one common S-RNase isoenzyme. Hungarian 'Orias' apricot cultivars showed different bands compared to the previous cultivars, but they shared completely identical patterns confirming that they possess the same S-genotype. 'Bergeron', `Harmat' and 'Korai zamatos' are characterised by an evidently distinct S-RNase pattern. The self-compatible cultivar (`Bergeron') had one allele, which suggests its correspondence to the Sc. Primers for the 2nd intron was unsuccessful in gaining fragments, which indicates that the 2nd intron in the Sc allele is too long to get any amplification. On the basis of our data, identities and differences were revealed in the S-allele constitution of some economically important Hungarian apricot cultivars at protein and DNA levels.